Amorphous Ni–Fe–Mo Suboxides Coupled with Ni Network as Porous Nanoplate Array on Nickel Foam: A Highly Efficient and Durable Bifunctional Electrode for Overall Water Splitting - Li, Yong‐Ke (Adv Sci (Weinh), 2020)
It is a great challenge to fabricate electrode with simultaneous high activity for the hydrogen evolution reaction (HER) and the oxygen evolution reaction (OER). Herein, a high‐performance bifunctional electrode formed by vertically depositing a porous nanoplate array on the surface of nickel foam is provided, where the nanoplate is made up by the interconnection of trinary Ni–Fe–Mo suboxides and Ni nanoparticles. The amorphous Ni–Fe–Mo suboxide and its in situ transformed amorphous Ni–Fe–Mo (oxy)hydroxide acts as the main active species for HER and OER, respectively. The conductive network built by Ni nanoparticles provides rapid electron transfer to active sites. Moreover, the hydrophilic and aerophobic electrode surface together with the hierarchical pore structure facilitate mass transfer. The corresponding water electrolyzer demonstrates low cell voltage (1.50 V @ 10 mA cm(−2) and 1.63 V @ 100 mA cm(−2)) with high durability at 500 mA cm(−2) for at least 100 h in 1 m KOH.